Réponses

  • Utilisateur Brainly
2014-09-30T20:54:30+02:00
A= 4 + 5 x (-3)
A= 4 + (- 15)
A= 4 - 15
A= - 11

C= -8 - 7 x (-4)
C= - 8 - (- 28)
C= - 8 + 28
C= 28 - 8
C= 20

B= ( 3 - 5 - 11 ) x 4
B= (- 2 - 11) x 4
B= - 13 x 4
B= - 52

D= -9 + (-15) : (-3) + 7
D= - 9 - 15 : (- 3) + 7
D= - 9 - (- 5) + 7
D= - 9 + 5 + 7
D= - 9 + 12
D= 12 - 9
D= 3
2014-09-30T21:35:59+02:00
A= 4 + 5 X (-3)               B= ( 3 - 5 - 11 ) x 4
A= 4 + (-15)                    B= ( 3 - 16 ) X 4
A= -11                            B= (-13) X 4
                                       B= 52

C= -8 - 7 x (-4)                 
C= -8 + 28   
C = 20

D= -9 + (-15) : (-3) + 7
D= -24 : 4
D= -7

Normalement c'est bon ;) 

                                           

Ouuh grosse erreur de ma part pour le D
Regarde sur la personne du dessus